2019
DOI: 10.5114/hm.2019.85094
|View full text |Cite
|
Sign up to set email alerts
|

Walking biomechanics and energetics of individuals with a visual impairment: a preliminary report

Abstract: Purpose. Although walking gait in sighted populations is well researched, few studies have investigated persons with visual impairments (VIs). Given the lack of physical activity in people with VIs, it is possible that reduced efficiency in walking could adversely affect activity. the purposes of this preliminary study were to (1) examine the biomechanics and energetics utilized during independent and guided walking in subjects with VIs, and (2) compare gait biomechanics between people with VIs and sighted con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
2
10
0
1
Order By: Relevance
“…This is also the first report of joint coordination for persons with complete blindness. In agreement with previous studies (Bennett et al, 2019; Hallemans et al, 2010; Nakamura, 1997), differences between persons who are blind and sighted controls found in this report appear to be mainly reduced stride length and joint ranges of motion, but occur without alterations of inter/intra-limb coordination. The findings from this preliminary report are interesting as proper locomotion (e.g., walking and running) mechanics are not formally taught in structured physical activity contexts (e.g., physical education settings) for persons who are blind (Holland et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This is also the first report of joint coordination for persons with complete blindness. In agreement with previous studies (Bennett et al, 2019; Hallemans et al, 2010; Nakamura, 1997), differences between persons who are blind and sighted controls found in this report appear to be mainly reduced stride length and joint ranges of motion, but occur without alterations of inter/intra-limb coordination. The findings from this preliminary report are interesting as proper locomotion (e.g., walking and running) mechanics are not formally taught in structured physical activity contexts (e.g., physical education settings) for persons who are blind (Holland et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have found reduced stride length and sagittal plane kinematics and increased energetic costs of walking in persons with varying levels of vision (Bennett et al, 2019; Hallemans et al, 2010; Kobberling et al, 1989; Nakamura, 1997). Although these previous studies illustrate some important differences between those with a VI and sighted controls, this preliminary study is the first to control for both walking speed (matched speeds for both independent and guided tasks) and subject anthropometrics (age, sex, and BMI).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Postural control deficits have also been found in visually impaired children with amblyopia and strabismus (Zipori et al 2018 ), suggesting that a moderate visual impairment is sufficient to interfere with postural stability. During walking, slower gait velocity, shorter stride length, limited ankle plantar flexion, and a prolonged duration of stance in blind children and adults compared to sighted control participants have been reported (Bennett et al 2019 ; Hallemans et al 2010 , 2011 ; Nakamura 1997 ). The altered gait patterns in the absence of vision have been interpreted as a more cautious walking strategy (Hallemans et al 2011 ; Nakamura 1997 ).…”
Section: Introductionmentioning
confidence: 99%